Molluscum contagiosum presenting as periorbital abscess in immunocompetent children - Moran Mor-Shaham; Joel Gutovitz; Oz Levinkron; Judit Krausz; Daniel Briscoe (Scientific Reports, 2023)
Abstract Molluscum contagiosum presenting as a periorbital region abscess is unusual. The virus generally causes a self-limiting localized disease in children. Presentation as an abscess has been reported mainly in immunocompromised patients. We performed a retrospective study of ten children treated for Molluscum contagiosum infection presenting as periorbital abscess. Data investigated included age, immunocompetence, systemic antibiotic treatment, clinical findings, and histopathology. All children were immunocompetent. Bacterial cultures taken in six of the ten children were positive in two. Seven patients received oral antibiotics before presentation but required IV antibiotics on admission. One patient received IV antibiotics only. All antibiotic treatment had very limited effect. Two patients had no antibiotic treatment. CT imaging in one case where orbital cellulitis was suspected showed no significant intraorbital findings with anterior involvement only. Nine out of ten children had surgery and intra-operative cryotherapy at our center with immediate improvement and recovery. One child whose parents initially refused surgical excision had initial limited clinical improvement of periorbital swelling with antibiotics. However, the lesions were excised shortly following discharge from our hospital at another medical center with a complete cure. Molluscum is a cause of periorbital abscess in immunocompetent children which should be part of the differential diagnosis in periorbital/adnexal infection. Antibiotic treatment has a limited effect, and the abscess is most likely a virally triggered reaction. Surgical excision and intra-operative cryotherapy are curative of the disease in our experience.